2021
DOI: 10.1038/s42003-021-02144-8
|View full text |Cite
|
Sign up to set email alerts
|

Eleven genomic loci affect plasma levels of chronic inflammation marker soluble urokinase-type plasminogen activator receptor

Abstract: Soluble urokinase-type plasminogen activator receptor (suPAR) is a chronic inflammation marker associated with the development of a range of diseases, including cancer and cardiovascular disease. The genetics of suPAR remain unexplored but may shed light on the biology of the marker and its connection to outcomes. We report a heritability estimate of 60% for the variation in suPAR and performed a genome-wide association meta-analysis on suPAR levels measured in Iceland (N = 35,559) and in Denmark (N = 12,177).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 85 publications
0
15
1
Order By: Relevance
“…NLRP3, a component of the NLRP3-inflammasome, is also a mediator of neuroinflammation and its dysregulation has been implicated in neurodegeneration ( Ising et al, 2019 ; Pellegrini et al, 2020 ). Plau is a gene related to aging and age-related diseases ( Cardoso et al, 2018 ) and has been suggested to exert chronic inflammatory effects ( Cardoso et al, 2018 ; Dowsett et al, 2021 ). Our integrated pathway analysis showed that neuroinflammation-related pathways ( Walker et al, 2022 ) such as Toll-like receptor signaling pathway, NOD-like receptor signaling pathway, cytokine-cytokine receptor interaction, NF-kB signaling pathways, JAK-STAT signaling pathway, PI3K-Akt signaling pathway, and Sphingolipid signaling pathway were the top-ranked KEGG pathways.…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3, a component of the NLRP3-inflammasome, is also a mediator of neuroinflammation and its dysregulation has been implicated in neurodegeneration ( Ising et al, 2019 ; Pellegrini et al, 2020 ). Plau is a gene related to aging and age-related diseases ( Cardoso et al, 2018 ) and has been suggested to exert chronic inflammatory effects ( Cardoso et al, 2018 ; Dowsett et al, 2021 ). Our integrated pathway analysis showed that neuroinflammation-related pathways ( Walker et al, 2022 ) such as Toll-like receptor signaling pathway, NOD-like receptor signaling pathway, cytokine-cytokine receptor interaction, NF-kB signaling pathways, JAK-STAT signaling pathway, PI3K-Akt signaling pathway, and Sphingolipid signaling pathway were the top-ranked KEGG pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to adaptable contributions by lifestyle, underlying chronic disease, and acute conditions, genetic predispositions also affect an individual’s tissue uPAR expression and blood suPAR level. In a recent genome-wide association study, we found that blood suPAR levels were under substantial genetic influence ( 30 ), with a heritability estimate of 60% and 13 independently genome-wide significant sequence variants associated with suPAR across 11 distinct loci. Associated variants were found in and around PLAUR as well as the gene encoding the uPAR ligand urokinase plasminogen activator (uPA, or urokinase) PLAU , the kidney-disease-associated gene PLA2R1 , and genes with relations to glycosylation, glycoprotein biosynthesis, and the immune response ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent genome-wide association study, we found that blood suPAR levels were under substantial genetic influence ( 30 ), with a heritability estimate of 60% and 13 independently genome-wide significant sequence variants associated with suPAR across 11 distinct loci. Associated variants were found in and around PLAUR as well as the gene encoding the uPAR ligand urokinase plasminogen activator (uPA, or urokinase) PLAU , the kidney-disease-associated gene PLA2R1 , and genes with relations to glycosylation, glycoprotein biosynthesis, and the immune response ( 30 ). This indicates that a combination of polymorphisms in different genes may affect the immune system and cause a higher basal level of suPAR.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated plasmin and plasminogen levels are common findings in severe COVID-19 illness as well as in patients with various chronic diseases, including hypertension, diabetes, and cardiovascular diseases. This may account for an unfavorable COVID-19 prognosis in patients with these disorders [214,215]. Moreover, SARS-CoV-2 may benefit from its association with Mycoplasma as this bacterium can directly block host immunoglobulins, protecting the virus [216,217].…”
Section: Rethinking Mycoplasmamentioning
confidence: 99%